Study of Socio-Demographic Factors in Pre Labour Rupture of Membranes in Rural Area (Global Journal of Medical Research, 2016)
Prelabor rupture of the fetal membranes (PLROM) is common obstetric problem and one of the most common clinical event where a pregnancy can turn into a high risk situation for mother as well as fetus. Present study was undertaken in a rural tertiary care institute located in central India with the aim to study the distribution and correlation of socio-demographic factors in PLROM. The overall incidence of PLROM is 6.02% of all deliveries during the study period. Majority belonged to age group of 21-25 years (57.62%). Occurrences of PROM was more among booked cases (61.90%). The incidence of PLROM was more in primigravida.